HOMOEOPATHIC TREATMENT OF MULTIPLE CANINE ORAL PAPILLOMA (WARTS) - A CASE REPORT - Muley, V D; Digraskar, S U; Sakhare, Meera; Khatke, P A; Kachave, K B; Jagade, V C; Ranjan, Rakesh; Rakh, B J (Indian Journal of Veterinary Sciences and Biotechnology, 2010)
Canine viral papillomatosis is commonly seen in dogs without any predilection to the specific breed or sex. Papillomatous lesions are always in multiple and affects the buccal mucosa, tongue, palate, pharynx, epiglottis, lips, eyelids and even on anus. The lesions begin as wide, flat, smooth, shiny papules of few millimeters in diameters and progress to whitish-gray, cauliflower-like hyperkeratotic masses up to 3 cm in diameter (Muller and Kirk, 1995). The present paper puts on record, a case of multiple oral papilloma (Warty excrescences) in a young dog and its successful treatment using homoeopathic remedies.
Keywords: ORAL; MULTIPLE CANINE ORAL PAPILLOMA; HOMOEOPATHIC